Bananas!* - Gertten, Fredrik (Sweden : WG Film ; Magic Hour Films, 2009)
Filmmaker Fredrik Gertten follows the American-Cuban lawyer Juan Domínguez as he represents 12 workers at a Nicaraguan banana plantation in a unique lawsuit against their employer Dole Food. The workers accuse Dole of having caused their infertility through the use of pesticide DBCP to protect its banana crops in 1982. This chemical's proven harmful effects had led to the United States to prohibit its use five years earlier. Dole was well aware of this, but continued to expose its foreign employees to the pesticide. Duane Miller pleads the workers' case in court in a classic David and Goliath scenario, but this Goliath is not about to be felled by a single well-aimed rock. With great aplomb, Dole's lawyer tries to undermine the illiterate workers' case by characterizing them as alcoholics and liars. The events following Gertten's completion of the film and preparations for its release on the festival circuit are worthy of a documentary in themselves. Dole Food tried to prevent screening of the film by accusing Gertten and his producers of disseminating lies. Gertten claimed his right to freedom of expression, but that did not stop Dole from taking legal action. Only after the Swedish Parliament expressed concern about Dole's attempts to impose censorship did the fruit company withdraw its complaint.
Coproduction: Denmark, Sweden. Verzio FF Submission
Duration: 01:20:00
Verzio Film Festival Submission
Keywords: Documentary films